2021
DOI: 10.48550/arxiv.2104.06211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Algebraic Dynamics of the Pentagram Map

Abstract: The pentagram map, introduced by Schwartz in 1992, is a dynamical system on the moduli space of polygons in the projective plane. Its real and complex dynamics have been explored in detail. We study the pentagram map over an arbitrary algebraically closed field of characteristic not equal to 2. We prove that the pentagram map on twisted polygons is a discrete integrable system, in the sense of algebraic complete integrability: the pentagram map is birational to a self-map of a family of abelian varieties. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In previous work, we showed that, in the planar case (N = 2), if n ≥ 4, the moduli space M 2 1,n is birational to P 2n , by working in explicit coordinates [22,Theorem 3.2]. This generalizes:…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In previous work, we showed that, in the planar case (N = 2), if n ≥ 4, the moduli space M 2 1,n is birational to P 2n , by working in explicit coordinates [22,Theorem 3.2]. This generalizes:…”
Section: Introductionmentioning
confidence: 76%
“…Note that the SL 3 -equivalence class of the monodromy T is an invariant of the pentagram map, providing two algebraically independent conserved quantities. In fact, the pentagram map is a discrete algebraic completely integrable system: it has an iterate which is birational to a translation on a family of abelian varieties [21,22]. But this is only a description of the generic behavior of the map.…”
Section: Introductionmentioning
confidence: 99%
“…The pentagram map, T 2 , is one of the best known discrete completely integrable system. See for instance, [1], [2], [3], [8], [9], [10], [11], [12], [14], [15], [21], [22]. The Pentagram Rigidity Conjecture would be a statement about the global topology of an abelian foliation associated to a completely integrable system if the map T 3 were known to be completely integrable.…”
Section: Contextmentioning
confidence: 99%
“…This implies in particular that the torus foliation discussed above is naturally an abelian fibration, with the individual tori having natural desciptions as Jacobian varieties for certain Riemann surfaces. Very recently, M. Weinreich [19] proved that T 2 is algebro-geometrically integrable in any field of characteristic not equal to 2. In [3], M. Glick related the pentagram map to a cluster algebra.…”
Section: Contextmentioning
confidence: 99%